Developmental toxicity of treated municipal wastewater effluent on Bombina orientalis (Amphibia: Anura) embryos. (April 2014) - Park, Chan Jin; Ahn, Hyo Min; Cho, Seong Chan; Kim, Tae‐Hoon; Oh, Jong‐Min; Ahn, Hong Kyu; Chun, Seung‐Hoon; Gye, Myung Chan
Abstract Amphibian populations have been decreasing in urban freshwater systems in Korea. To elucidate the biological safety of treated wastewater effluent (TWE) in the Tancheon basin, the capital area of Korea, a 7‐d–exposure Bombina orientalis embryo developmental toxicity assay was examined during the breeding season. In March, there were no significant differences in embryonic survival or malformation among the water samples. In July, following monsoon precipitation, embryonic lethality in TWE was significantly higher than in the upstream water sample. Malformation in TWE and TWE‐mixed waters was significantly higher than in the control and upstream water samples. Tail muscle height of tadpoles also significantly decreased in TWE and TWE‐mixed waters. Heavy metals were not detected in any samples. Total nitrogen, total phosphorous, and chemical oxygen demand in TWE markedly increased together with a decrease in dissolved oxygen in July. The increase in organic and inorganic loading following precipitation could have made TWE and TWE‐mixed water not suitable for embryonic development. Though being managed based on physicochemical criteria, the water quality of TWE may not be sufficient to assure normal development of amphibian embryos. An amphibian developmental toxicity assay would be helpful for the water‐quality management of TWE and urban freshwater systems in Korea. Environ Toxicol Chem 2014;33:954–961. © 2014 SETAC